Bees in a Heat Island: Bee Assemblages on Cercis canadensis and Cornus florida in Urban and Exurban Sites - Camilo, Gerardo R.; Fogel, Nina S.; Mullikin, Jenny C.; Moss, Alan; Edens-Meier, Retha M.; Bernhardt, Peter (Journal of Pollination Ecology, 2025)
The predicted effects of climate change on pollination processes are multiple, including earlier blooming times and decoupling from pollinators. Yet, little research has been conducted, especially in urban areas where the heat island effect is known to speed up warming. Our aim is to investigate which bee species visit two native, vernal-blooming tree species with continuous distributions from urban to exurban sites. In 2019 and 2020, we collected bees on the native, mass-flowering Cercis canadensis and Cornus florida in the St. Louis metropolitan and exurban areas in Missouri, USA. A total of 434 bees carrying pollen were collected identifying 54 species representing five families. An additional 123 specimens which did not carry any pollen at all were captured representing 37 species within five families. We observed a greater species diversity among pollen carrying bees at exurban sites while the numbers of male bees collected were proportionately higher in urban versus exurban sites. Although flowering periods of the two tree species overlapped, the pollen of both tree species was identified on only 34 bees.